Female Ulama and Islamic Education in Manado: Pedagogical Authority in a Muslim Minority Context - Salim, Arhanuddin (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2026)
This study examines how female ulama in Manado construct and negotiate religious authority through Islamic education within a Muslim-minority and multicultural context. Using a qualitative design grounded in Interpretative Phenomenological Analysis (IPA), the study draws on in-depth interviews with seven female ulama actively engaged in community-based Islamic education in Manado, North Sulawesi. Interviews were conducted between March and July 2024 in Bahasa Indonesia, audio-recorded, transcribed verbatim, and analyzed through iterative coding, theme development, and cross-case interpretation following IPA procedures. The findings reveal that female ulama primarily exercise authority outside formal religious institutions. They construct legitimacy through sustained pedagogical engagement, moral credibility, and culturally adaptive teaching practices. Islamic teachings are transmitted largely through informal learning spaces such as majelis taklim, family-based instruction, and digital platforms. These spaces emphasize coexistence, civic ethics, and ethical modeling rather than doctrinal assertion. Religious authority in this context is therefore relational and pedagogically negotiated rather than institutionally granted. This study contributes to Islamic education scholarship by demonstrating how pedagogical authority emerges through relational teaching, ethical modeling, and cultural adaptation in Muslim-minority contexts. The findings offer practical insights for strengthening inclusive and community-responsive Islamic education.